EXPEDIENCE OF APPLICATION MODERN TECHNOLOGIES IN THE SYSTEM OF SCHOOLCHILDREN'S PHYSICAL EDUCATION IN UKRAINE (Fiep Bulletin - online, 2016)
.
Keywords: Physical education; innovative technologies; impellent activity.